Performance Evaluation of CO2 EOR in Tight Oil Formations with Complex Fracture Geometries - Zuloaga Molero, Pável (2016)
Descargue el texto completo en el repositorio institucional de la University of Texas at Austin: http://hdl.handle.net/2152/39374